تحليل واقع التمويل المصرفي للقطاع الصناعي في سورية - هرمز, نور الدين; يوسف, بهاء الدين (Latakia University Journal - Economic and Legal Sciences Series, 2016)
يتناول هذا البحث وبالتحليل الاقتصادي – القياسي واقع القطاع المصرفي في سورية ، ومدى مساهمته في تمويل القطاعات الاقتصادية، وخاصة القطاع الصناعي. من خلال دراسة القروض المقدمة من المصارف المتخصصة للقطاعات الاقتصادية في سورية من جهة, ومن جهة أخرى دراسة العلاقة القائمة ما بين حجم قروض المصرف الصناعي والاستثمار الصناعي في سورية. ليتوصل البحث إلى عدد من الحلول والمقترحات التي يمكن أن تسهم في زيادة فعالية وكفاءة وأداء القطاع المصرفي ليؤدّي دوراً أكثر فعالية في تنمية القطاع الصناعي, باعتباره من أهم القطاعات الاقتصادية المحركة لباقي القطاعات ،ولعملية التنمية الاقتصادية والاجتماعية. This research deals with the standard economic analysis of the reality of the banking sector in Syria, and the extent of its contribution to the financing of economic sectors, especially the industrial sector. Through study loans from banks specialized economic sectors in Syria on the one hand, the other hand, the study of the relationship between industrial bank loans, and industrial investment in Syria. To reach to a number of solutions and proposals that could contribute to increasing the effectiveness and the efficiency and performance of the banking sector to play a more active role in the development of the industrial sector, as one of the most important sectors of the economy for the rest of the driving sectors and the process of economic and social development.